3x(x+1)-5=x(3x+2)+11

Simple and best practice solution for 3x(x+1)-5=x(3x+2)+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(x+1)-5=x(3x+2)+11 equation:


Simplifying
3x(x + 1) + -5 = x(3x + 2) + 11

Reorder the terms:
3x(1 + x) + -5 = x(3x + 2) + 11
(1 * 3x + x * 3x) + -5 = x(3x + 2) + 11
(3x + 3x2) + -5 = x(3x + 2) + 11

Reorder the terms:
-5 + 3x + 3x2 = x(3x + 2) + 11

Reorder the terms:
-5 + 3x + 3x2 = x(2 + 3x) + 11
-5 + 3x + 3x2 = (2 * x + 3x * x) + 11
-5 + 3x + 3x2 = (2x + 3x2) + 11

Reorder the terms:
-5 + 3x + 3x2 = 11 + 2x + 3x2

Add '-3x2' to each side of the equation.
-5 + 3x + 3x2 + -3x2 = 11 + 2x + 3x2 + -3x2

Combine like terms: 3x2 + -3x2 = 0
-5 + 3x + 0 = 11 + 2x + 3x2 + -3x2
-5 + 3x = 11 + 2x + 3x2 + -3x2

Combine like terms: 3x2 + -3x2 = 0
-5 + 3x = 11 + 2x + 0
-5 + 3x = 11 + 2x

Solving
-5 + 3x = 11 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-5 + 3x + -2x = 11 + 2x + -2x

Combine like terms: 3x + -2x = 1x
-5 + 1x = 11 + 2x + -2x

Combine like terms: 2x + -2x = 0
-5 + 1x = 11 + 0
-5 + 1x = 11

Add '5' to each side of the equation.
-5 + 5 + 1x = 11 + 5

Combine like terms: -5 + 5 = 0
0 + 1x = 11 + 5
1x = 11 + 5

Combine like terms: 11 + 5 = 16
1x = 16

Divide each side by '1'.
x = 16

Simplifying
x = 16

See similar equations:

| 4x^2-121+y^2=0 | | -37-5k=-2-2(4+7k) | | 4x-2x=-7x+18 | | -4(m-7)=32-2m | | 1x+4(x+5)=40 | | 10y=2y+7+7t | | 4(u-8)-9=-5(-6u+5)-8u | | -6(8k+5)+7k=-30+5k | | y=-3x^2+10x-3 | | 12x+y=35 | | -29=5(2a-1)+-2 | | 7(n-2)=-10+8n | | y=-2x^2+4x+20 | | -39-6n=-3(n+6) | | 2(x-5)-7=3(x+3) | | -4(8x-7)=3-7x | | -0.1x^2+0.1x-.01=0 | | 2[3x+7]=4x-4 | | 14[3x-2(x+4)]=28 | | -0.1x^2+0.1x=-.01 | | 8x-7x-7=-7 | | (m^3-2m+1)(m^2-m+2)= | | -13=3*(-5)+2 | | -x+10=22 | | y+4=3y+9 | | 5000p+500=90 | | (x*15)+28=(x*5)+218 | | 3*x-3+5=14 | | 3y-3x=6x-15 | | 2x+10=3x-4 | | (x+1)(x^5-x^4+x^3-x^2+x-1)= | | (X+2)(x-2)=21 |

Equations solver categories